2014
DOI: 10.1371/journal.pone.0090936
|View full text |Cite
|
Sign up to set email alerts
|

Expression Level and Subcellular Localization of Heme Oxygenase-1 Modulates Its Cytoprotective Properties in Response to Lung Injury: A Mouse Model

Abstract: Premature infants exposed to hyperoxia suffer acute and long-term pulmonary consequences. Nevertheless, neonates survive hyperoxia better than adults. The factors contributing to neonatal hyperoxic tolerance are not fully elucidated. In contrast to adults, heme oxygenase (HO)-1, an endoplasmic reticulum (ER)-anchored protein, is abundant in the neonatal lung but is not inducible in response to hyperoxia. The latter may be important, because very high levels of HO-1 overexpression are associated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 55 publications
7
31
0
Order By: Relevance
“…In neonatal HO-1 null mutant mice and WT littermates exposed to hyperoxia for 3 days and allowed to recover in room air for 11 days, six DNA damage-response genes were down-regulated in the WT; whereas these were up-regulated many-fold in the knockout, suggesting that HO-1 disruption modifies DNA repair pathways which are important in tumorigenesis (115). We also show that transgenic mice with cytoplasmic over-expression of HO-1 in type II cells exposed to 3 days of hyperoxia as neonates had increased numbers of multinucleated hyper-proliferating type II cells and foamy macrophages but no evidence of fibrosis or inflammation (69). This correlated with lung lesions on MRI with enhanced p-ERK (which is seen in early tumorigenesis) and PCNA staining (69).…”
Section: Maladaptive Consequences Of Ho-1 Overexpression and Cellularmentioning
confidence: 61%
See 4 more Smart Citations
“…In neonatal HO-1 null mutant mice and WT littermates exposed to hyperoxia for 3 days and allowed to recover in room air for 11 days, six DNA damage-response genes were down-regulated in the WT; whereas these were up-regulated many-fold in the knockout, suggesting that HO-1 disruption modifies DNA repair pathways which are important in tumorigenesis (115). We also show that transgenic mice with cytoplasmic over-expression of HO-1 in type II cells exposed to 3 days of hyperoxia as neonates had increased numbers of multinucleated hyper-proliferating type II cells and foamy macrophages but no evidence of fibrosis or inflammation (69). This correlated with lung lesions on MRI with enhanced p-ERK (which is seen in early tumorigenesis) and PCNA staining (69).…”
Section: Maladaptive Consequences Of Ho-1 Overexpression and Cellularmentioning
confidence: 61%
“…Despite the cytoprotective effects of moderate HO-1 overexpression, we have shown that at high levels, HO-1 may be deleterious (108), resulting in enhanced oxidative stress and apoptosis and decreased cell proliferation in vitro (99) and, when targeted to type II cells in vivo, this leads to a maladaptive over-proliferation of type II cells and perhaps a failure to differentiate to type I cells which are important for recapitulation of the normal alveolar epithelium. This then manifests as increased alveolar thickness and decreased lung function (69). In neonatal rats exposed to hyperoxia, no significant increase in lung HO-1 mRNA was seen in contrast to similarly exposed adults (21).…”
Section: Maturation Alters the Role And Regulation Of Ho-1 In Oxidatimentioning
confidence: 98%
See 3 more Smart Citations